2021
DOI: 10.1021/jacsau.1c00254
|View full text |Cite
|
Sign up to set email alerts
|

Markov State Models to Study the Functional Dynamics of Proteins in the Wake of Machine Learning

Abstract: Markov state models (MSMs) based on molecular dynamics (MD) simulations are routinely employed to study protein folding, however, their application to functional conformational changes of biomolecules is still limited. In the past few years, the field of computational chemistry has experienced a surge of advancements stemming from machine learning algorithms, and MSMs have not been left out. Unlike global processes, such as protein folding, the application of MSMs to functional conformational changes is challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 102 publications
1
69
0
Order By: Relevance
“…We note, however, that there are other ways to obtain these representative conformations. Metastable states can be obtained from Markov state models (MSM) from multiple short MD simulations as long-lived conformations in the dynamics of the system . This analysis can help characterize the conformational space of unbound aptamers and the arrangement of binding sites .…”
Section: Discussionmentioning
confidence: 99%
“…We note, however, that there are other ways to obtain these representative conformations. Metastable states can be obtained from Markov state models (MSM) from multiple short MD simulations as long-lived conformations in the dynamics of the system . This analysis can help characterize the conformational space of unbound aptamers and the arrangement of binding sites .…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by such consideration, numerous molecular dynamics (MD) [37][38][39][40][41][42][43][44] and enhanced sampling simulations 33,[45][46][47] have been performed to investigate conformational properties of Ras [48][49][50] and to dissect their biological function. Lu et al 51 observed that KRasGTPÁMg 2+ had one active state and three inactive substates in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Markov state model was developed to connect the information from individual trajectories to by building transition network between distinct states. [78][79][80] In markovian processes, the future step of the process should only depend on present states, not on the past states. S23A and S23B).…”
Section: Markov State Modelsmentioning
confidence: 99%